2013
DOI: 10.1080/00380768.2013.817938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land-use type and nitrogen addition on nitrous oxide and carbon dioxide production potentials in Japanese Andosols

Abstract: Land-use type and nitrogen (N) addition strongly affect nitrous oxide (N 2 O) and carbon dioxide (CO 2 ) production, but the impacts of their interaction and the controlling factors remain unclear. The aim of this study was to evaluate the effect of both factors simultaneously on N 2 O and CO 2 production and associated soil chemical and biological properties. Surface soils (0-10 cm) from three adjacent lands (apple orchard, grassland and deciduous forest) in central Japan were selected and incubated aerobical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 54 publications
3
4
0
Order By: Relevance
“…This pattern of emission was due to rapid mineralization of the readily decomposable soil organic carbon [ 44 ]. Our result for CO 2 production was in close agreement with the study of Kong et al [ 45 ], which also observed the highest CO 2 production during the initial phase of the incubation, and then it decreased with incubation time.…”
Section: Discussionsupporting
confidence: 93%
“…This pattern of emission was due to rapid mineralization of the readily decomposable soil organic carbon [ 44 ]. Our result for CO 2 production was in close agreement with the study of Kong et al [ 45 ], which also observed the highest CO 2 production during the initial phase of the incubation, and then it decreased with incubation time.…”
Section: Discussionsupporting
confidence: 93%
“…It can be observed that in the initial stage of our study (on day 4), the CO 2 flux was highest from all the treated soils. This result is in line with the studies of Kong et al [81] and Wang et al [82]. The plausible mechanism was the decomposable soil organic carbon's rapid mineralization [83].…”
Section: Combined Application Of Biochar and Lime Accelerated Soil Co 2 Emissionsupporting
confidence: 91%
“…In our study, soil CO 2 emission rate was faster during the first 15 days, and then decreased gradually until the end of incubation. The result was consistent with the findings of Kong et al (2013) and Amin (2020), and the phenomenon was due to the rapid mineralization of readily decomposable organic carbon in the soil initially. As the incubation process continued, the easily decomposable organic carbon in the soil was consumed preferentially by the microbes, while it needed a relatively long time for the consumption of the hardly decomposable substances by microbes, which led to a gradual decrease of CO 2 emission rate (Oo et al 2018).…”
Section: Discussionsupporting
confidence: 90%